The Student-Created Poster: A WebQuest Active Learning Strategy in Online Environments - Hilda Rakerda; Nur Arifah Drajati; Ngadiso Ngadiso (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
Posters are one of the school project artifacts that students could create to engage themselves in their knowledge building at school. Combine with WebQuest as the active learning instruction platform in an online learning, creating posters increase students’ engagement, build interest in topic learned, inspire higher-level independent thinking, and motivate student on their personal learning experiences. The aim of this study was to investigate student-created poster as an active learning approach in an online environment using WebQuest to inform instructional practices of student-created poster. This study used a case study method to explore the phenomenon occurred during the elective English course in the first grade of senior high school at Indonesia. Data analyzed in this study included 21 high school students, students’ posters and the classroom observation done in 5 weeks.  The finding of this qualitative study revealed that student-created poster utilizing WebQuest as the instructional learning method was an active learning activity that improve students perception of self-efficacy in comprehend the reading text and write the information in poster and evidence of student engagement of behavioral, affective and cognitive domains. Themes derived from the perception of the participants included: perceived self-efficacy, the novelty or usefulness of creating a poster, and the technical and content knowledge. Student-created poster as an active approach using WebQuest can be included in the context of High School English learning to enhance the English skills of students and foster integrative skills of the 21st century. Practical implications for teachers when designing poster assignments created by students using WebQuest include (a) following a model for the development of posters; (b) providing extra time for content acquisition and revisions; and (c) incorporating group evaluation.